ISRĀ’ILIYYĀT NARRATIVES IN IBN KATHĪR’S TAFSĪR: METHODOLOGICAL PERSPECTIVES AND THEIR IMPLICATIONS FOR QUR’ANIC STUDIES - Supriyanto Supriyanto; El Hassen Sid Ahmed El Habib (Sekolah Tinggi Agama Islam Sadra, 2026)
The presence of isrā’iliyyāt narratives within the tradition of Qur’anic exegesis has long been a subject of scholarly debate, particularly concerning the extent to which narratives originating from earlier religious traditions may be used in the interpretation of Qur’anic verses. Among classical exegetes, Tafsīr al-Qur’ān al-Aẓīm, the work of Ibn Kathīr, is widely recognized for its strong reliance on transmitted reports (riwāyat) in the interpretation of the Qur’an. Within this framework, Ibn Kathīr’s tafsir frequently engages with isrā’iliyyāt narratives that appear in earlier exegetical materials. This study aims to analyze how Ibn Kathīr evaluates and manages isrā’iliyyāt narratives in his tafsir and to identify the interpretive patterns he employs when dealing with such reports. Using a qualitative method through textual analysis combined with an intertextual approach, this research examines selected isrā’iliyyāt narratives cited in Ibn Kathīr’s tafsir and analyzes how these narratives are interpreted, assessed, and contextualized. The findings indicate that Ibn Kathīr adopts a selective and critical evaluative framework in dealing with isrā’iliyyāt. Although he pays attention to the chain of transmission (sanad), his assessment does not rely solely on sanad verification. He also evaluates the content of these narratives, particularly by comparing them with Qur’anic verses and authenticated prophetic traditions. Reports that contradict established Islamic theological principles or authentic hadith are explicitly rejected, whereas narratives that do not conflict with the core teachings of Islam are occasionally used cautiously to supplement the historical context or narrative details of particular verses. These findings demonstrate that Ibn Kathīr’s engagement with isrā’iliyyāt is not an uncritical accommodation but rather operates within a structured interpretive framework that integrates both transmission criticism and content evaluation.